Oestrogen Detoxification Ability of White Rot Fungus Trametes hirsuta LE-BIN 072: Exoproteome and Transformation Product Profiling - Olga S. Savinova; Tatiana S. Savinova; Tatyana V. Fedorova (Journal of Fungi)
White rot fungi, especially representatives of the genus Trametes spp. (Polyporaceae), are effective destructors of various xenobiotics, including oestrogens (phenol-like steroids), which are now widespread in the environment and pose a serious threat to the health of humans, animals and aquatic organisms. In this work, the ability of the white rot fungus Trametes hirsuta LE-BIN 072 to transform oestrone (E1) and 17β-oestradiol (E2), the main endocrine disruptors, was shown. More than 90% of the initial E1 and E2 were removed by the fungus during the first 24 h of transformation. The transformation process proceeded predominantly in the direction of the initial substrates’ detoxification, with the radical oxidative coupling of E1 and E2 as well as their metabolites and the formation of less toxic dimers in various combinations. A number of minor metabolites, in particular, less toxic estriol (E3), were identified by HPLC-MS. The formation of E1 from E2 and vice versa were shown. The exoproteome of the white rot fungus during the transformation of oestrogens was studied in detail for the first time. The contribution of ligninolytic peroxidases (MnP5, MnP7 and VP2) to the process of the extracellular detoxification of oestrogens and their possible metabolites is highlighted. Thus, the studied strain appears to be a promising mycodetoxicant of phenol-like steroids in aquatic environments.